Ánalisis financiero en una empresa comercial Ventas y Algo Mas E.I.R.L. - 2019 - Lopez Santillan, Luris Magdalena (2022)
With this research work, we obtain an encouraging result that the companies, should apply their respective analysis to their financial statements, being its main objective of my thesis: "Financial Analysis in a Commercial Company Sales and Something More EIRL-2019", this thesis is of descriptive qualitative type, its study population is 25 people, workers, staff and owners of companies of this type. We have as a conclusion, efficient 64%, that the companies will have an optimal and favorable result in their financial statements, if they apply their respective analysis to these statements, in the data system we also obtain 08% of deficient, in terms of ignorance and non-application of these financial analysis, of the partners and accountants. The lack of knowledge of the application of the analysis to the financial statements on the part of the main shareholders and accounting professionals, affects these companies, because their financial statements will not be expressed in a real way and their tax payments, also will not be true, affecting the income to the state, likewise their results also will not reflect confidence in front of the banks, so that they are creditors of loans.